2015
DOI: 10.1177/1934578x1501000628
|View full text |Cite
|
Sign up to set email alerts
|

A Novel One-step Synthesis of Quinoline-2(1H)-thiones and Selones by Treating 3-Aryl-3-(2-aminophenyl)-1-propyn-3-ols with a Base and Elemental Sulfur or Selenium

Abstract: A one-step conversion of 3-aryl-3-(2-aminophenyl)-1-propyn-3-ols into quinoline-2(1H)-thiones and quinoline-2(1H)-selones was achieved only by treating the substrates with n-butyllithium and either elemental sulfur or selenium, respectively. The reactions were assumed to proceed through an intramolecular nucleophilic attack of the neighboring amino group to the plausible in situ generated reactive species related to chalcogenoketenes. The subsequent mCPBA oxidation of quinoline-2(1H)-selones afforded quinolin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…In the course of our successive studies on the synthesis of higher-row chalcogenocarbonyl compounds, we have found a convenient synthesis of dialkenyl diselenides C through the reaction of ptoluenesulfonylhydrazones A, derived from ketones possessing an α-methylene group, with a base and elemental selenium. [18][19][20][21][22][23][24] The reaction was assumed to proceed through the in situ generated alkeneselenolate ions B via Bamford-Stevens type reaction of ptoluenesulfonylhydrazones [25][26][27][28][29][30][31][32][33] as shown in Scheme 1, and, therefore, the synthetic application of this sequence to the preparation of various selenium-containing heterocyclic compounds was keenly expected.…”
mentioning
confidence: 99%
“…In the course of our successive studies on the synthesis of higher-row chalcogenocarbonyl compounds, we have found a convenient synthesis of dialkenyl diselenides C through the reaction of ptoluenesulfonylhydrazones A, derived from ketones possessing an α-methylene group, with a base and elemental selenium. [18][19][20][21][22][23][24] The reaction was assumed to proceed through the in situ generated alkeneselenolate ions B via Bamford-Stevens type reaction of ptoluenesulfonylhydrazones [25][26][27][28][29][30][31][32][33] as shown in Scheme 1, and, therefore, the synthetic application of this sequence to the preparation of various selenium-containing heterocyclic compounds was keenly expected.…”
mentioning
confidence: 99%
“…In the course of our studies on the cumulated chalcogenocarbonyl compounds, we previously reported a novel and convenient synthesis of unsaturated thioamides and selenoamides through the reaction of substituted propargyl methyl ethers A with a base, elemental sulfur or selenium, and a primary or secondary amine. These reactions were assumed to proceed through in situ generation of some heterocumulene-like intermediates related to propadienethiones C and selones D [2] and the subsequent nucleophilic addition of amine. These successful results derived us to envisage an extension of the method to the synthesis of 2-alkenecarbodithioate esters B, widely recognized as versatile building blocks for a variety of sulfur-containing heterocycles [3], through a similar treatment by applying a sulfur nucleophile in place of amine, and finally we found a new one-pot preparation of compounds B from 3,3disubstituted propargyl ethers A by the stepwise treatment of a base, elemental sulfur, and a thiol.…”
mentioning
confidence: 99%